Connective Tissue Growth Factor in Patients with Coronary Heart Disease: a Pilot Study - Svetlana V. Topolyanskaya; Tatyana A. Eliseeva; Olga I. Turna; Olga N. Vakulenko (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
AIM. To determine the concentration of connective tissue growth factor and assess the relationship of this index with a number of pathological conditions in elderly patients with CHD. MATERIAL AND METHODS. The study enrolled 50 patients older than 75 years with a diagnosis of coronary heart disease (CAD); most of them (71%) were women. The patients ranged in age from 75 to 96 years (mean age -87.8 years). The concentration of connective tissue growth factor (CTGF) in blood was determined by enzyme immunoassay. RESULTS AND DISCUSSION. In the group of CHD patients, the average CTGF concentration was 357.2 pg/ml, whereas in healthy young adults it was 1076.7 pg/ml (p=0.07). Only 7.9% of patients with CHD had CTGF level exceeding 1000 pg/ml, whereas in young subjects CTGF level exceeded 1000 pg/ml in 25% of cases. In patients with clinically significant CHD, CTGF concentration was significantly higher than in patients without CHD (p=0.001). A negative correlation was registered between the CTGF levels and the systolic (r = -0.25; p = 0.1) and diastolic (r = -0.36; p = 0.02) blood pressure. In the subgroup of patients with pneumosclerosis, the median CTGF concentration reached 190.7 pg/l, without it - 34.7 pg/ml (p = 0.03). A significant inverse correlation was found between the CTGF levels and glucose (r = -0.34; p = 0.03), total cholesterol (r = -0.49; p = 0.002) and LDL cholesterol (r = -0.40; p = 0.01) concentrations. This pilot study found a significant effect of CTGF on echocardiographic parameters and the course of CHD, and higher levels of CTGF in patients with pneumosclerosis. However, a small sample of patients and extremely variable CTGF values do not currently allow unequivocal conclusions to be drawn at this time about the role of this factor in various comorbid conditions. CONCLUSION. Further research is needed to establish the clinical significance of CTGF.